Multi-Platform System Development for Violence Complaint Services using the CodeIgniter Framework - Rohmah, Putri Anjilis; Setiaji, Pratomo; Muzid, Syafiul (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Violence against women and children remains a prevalent social issue in Indonesia, including in Kudus Regency. The lack of fast, secure, and easily accessible reporting facilities is one of the factors contributing to the low reporting rate, leaving many cases unaddressed. This study aims to design and develop a web-based violence complaint information system using the CodeIgniter framework with a Model-View-Controller (MVC) architecture to ensure a more structured, secure, and efficient system. The development method follows the waterfall model, consisting of requirements analysis, design, implementation, integration, and system testing. The system provides key features such as an online reporting form, automated notifications to officers, real-time report status tracking, and case progress recording by authorized personnel. Black-box testing conducted by one reporter and three staff members of the Kudus Social Service (Dinas Sosial P3AP2KB) on six main features across four different scenarios resulted in a total of 96 test cases, achieving a functional success rate of 98.9%. One failure was identified in file upload validation, where the system still allowed unsupported file formats. Nevertheless, all other features functioned properly, and the system was proven responsive across devices. This reliability supports faster reporting and case handling, enabling victims to report more easily while allowing relevant institutions to respond quickly, accurately, and transparently.